DRUG UTILIZATION AND PRESCRIBING PATTERN ANALYSIS IN ORTHOPAEDIC OUTPATIENT DEPARTMENT OF TERTIARY CARE HOSPITAL - K, DHIVYA; SHANKARI R, SHIVA; ZULKARNANE A, MOHAMMED; R, GAUTAM (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of conducting prescribing pattern study is to monitor, evaluate, and if necessary, recommend modifications in the prescribing behavior of medical practitioners. Hence, this study was conducted to analyze the drug utilization and prescribing pattern of drugs in orthopedic outpatient department (OPD). Methods: This prospective observational study was conducted in the orthopedic OPD of tertiary care hospital for a period of 3 months. Data were obtained from the prescriptions through one-to-one interviews and recorded in a separately designed case report form. Results: Out of the 260 patients enrolled in the study, 181 were female and 79 were male. The patients between the ages of 50 and 60 years constituted the higher number with a mean age of 52.2 years. The total number of drugs prescribed in the analyzed prescriptions was 1012 which includes orthopedic drugs as well as drugs prescribed to treat various comorbidities. The World Health organization drug prescribing indicators were used to assess the appropriate use of drugs. Conclusion: Our study concludes that drug utilization and prescribing quality should be improved by promoting medical education on current updates. The periodic audit should be conducted by a clinical pharmacist to reduce an error in the prescription as well as to check the compliance of prescription with standard treatment guidelines for rationalizing the therapy.